PEMBERDAYAAN MASYARAKAT BERBASIS TRADISI LOKAL STUDI KELURAHAN KALAODI TIDORE KEPULAUAN-MALUKU UTARA - Kamaruddin Salim (Jurnal Ilmu dan Budaya, 2020)
Tradition-based community empowerment that is carried out is an empowerment process carried out by the community by developing a joint work program based on traditional values or cultural identities that exist and are grounded in society without eliminating that cultural identity. This study aims to explore and identify the potential of community social capital in Kalaodi village, namely: Informal institutions and institutions such as community socio-economic networks, traditional institutions and traditional ceremonies in the form of paca goya, working groups and marong (mutual cooperation) and community social action. in conducting empowerment based on community self-help. In addition, this study is to determine the efforts of the people of Kalaodi in empowering communities based on local traditions. Community empowerment is carried out in the form of management and utilization of village gardens and youth gardens in which cloves and nutmeg are produced, used for building village road infrastructure and building community learning facilities, in the form of a reading house in Dola village. This research uses descriptive analysis method, data collection, observation, interview and document study. The results showed the empowerment carried out by villagers in the use of natural products which was accompanied by assistance from government officials and community organizations.